Penerapan Model Pembelajaran Bahasa Berbasis Tugas (TBLT) dan Materi Otentik dalam Pembelajaran Reading Comprehension di SMA Negeri 2 Kota Ternate - Sutisno Adam; Sulmi Magfirah (LPPM Universitas Bumigora Mataram, 2020)
Convensional Learning Model, such as lecturing method which makes teacher as the learning center without notice to the activeness and participation of students in the classroom still becomes teachers’ favourite style in teaching reading comprehension. Consequently, the learning process tends to be monotonous. This factor can answer the reason why the students’ achievement in reading skill at SMA 2 Ternate is not optimal. Then, this is suspected to be a factor in the occurrence of these problems. Therefore, the researcher applied TBLT (Task Based Language Teaching) and combine it with authentic material in reading comprehension. This research is a quasi-experimental research with the nonequivalent pretest-posttest group design. The total population of this study were students of XI SMA Negeri 2 Ternate, who were class XI students of SMA Negeri 2 Kota Ternate. One of the XI classes was used as the experimental class and another one became the control class, then it analyzed by using SPSS 20.0. The selection of the class was based on the observation to see the similarity of students' abilities in these classes. The result showed that the TBLT method combined with the authentic material in the Reading Comprehension could increase: (1) the learning motivation of XI SMA 2 Ternate students; (2) increasing the student learning outcomes. It can be seen from the results of the Paired Sample t-test table that the significance = 0.000 is less than the significant level (α) = 0.05, then H0 is rejected. Therefore, it can be concluded that there has been an increasing of learning outcomes in the experimental class from pre-test to post-test. Based on the result, the TBLT method can be recommended as a method used to increase English learning motivation.